THE ROLE RESILIENCE AND ACADEMIC SELF-EFFICACY IN INCREASING ACADEMIC ENGAGEMENT OF UNDERGRADUATE NURSING STUDENTS - Kiftiyah, Kiftiyah; Farida, Ika Andrini; Wiyono, Bambang Budi; Hitipeuw, Imanuel (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2024)
Academic Engagement is an important concern considering that nursing students will be directly involved with patients and provide nursing care to patients directly. Ideally, undergraduate nursing students in the emerging adulthood phase have a high level of academic engagement. However, reality shows that there are still many students with relatively low levels of academic engagement. This will later have an impact on low academic achievement, low student competence, increased disengagement and increased drop out rates among students. Previous research results show that academic engagement is related to academic resilience and academic self-efficacy. Therefore, the aim of this research is to determine the influence of academic resilience and academic self-efficacy on the academic engagement of undergraduate nursing students. This type of research is correlational with a cross-sectional approach. The research sample was 312 undergraduate nursing students from STIKes Dian Husada Mojokerto with a sampling technique using stratified random sampling. Statistical analysis uses multiple linear regression. The research results show that academic resilience and academic self-efficacy influence the academic engagement of nursing students.